Analisis Pengaruh Jenis-Jenis Pemeriksaan Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Badan (Studi Kasus pada KPP Surabaya Wonocolo) - Ali Muhdor (AKUNTANSI 45, 2022)
Tax is one of the most potential state revenues and is the backbone of state revenue in the State Revenue and Expenditure Budget (APBN). The purposes of this study are 1. To find out whether there is a partial effect of the types of tax audits on the level of compliance of corporate taxpayers at the Pratama Surabaya Wonocolo Tax Service Office? 2. To find out whether there is a simultaneous effect on the level of corporate taxpayer compliance at the Pratama Surabaya Wonocolo Tax Service Office? The results of data analysis obtained from testing the dominant influence is the Tax Audit Selection Criteria with a correlation coefficient of 0.816. This shows that there is a very strong positive correlation between the selection criteria for tax audits and taxpayer compliance at KPP Pratama Surabaya Wonocolo. The hypothesis reveals that there is no effect of routine tax audits on taxpayer compliance at KPP Pratama Surabaya Wonocolo with a large effect of only 15.7%, while the selection criteria for tax audits has an effect of 40.3%. This study provides empirical evidence that routine tax audits have no significant effect on taxpayer compliance at KPP Pratama Surabaya Wonocolo.